2013
DOI: 10.1007/s00404-013-3017-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression and significance of biglycan in endometrial cancer

Abstract: Biglycan might play a role in the progression of human endometrial cancer and it might be a useful molecular marker for the prognosis of endometrial cancer. This research is an initial step towards biglycan as a potential prognosis marker in endometrial cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 14 publications
2
41
0
Order By: Relevance
“…In previous study, we have confirmed that BGN is overexpressed in endometrial cancer [13]. In present study, we first screened the higher expression of BGN in several endometrial cancer cell types by Western blot, and then we explored the function of BGN in vitro and in vivo.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…In previous study, we have confirmed that BGN is overexpressed in endometrial cancer [13]. In present study, we first screened the higher expression of BGN in several endometrial cancer cell types by Western blot, and then we explored the function of BGN in vitro and in vivo.…”
Section: Introductionsupporting
confidence: 68%
“…Our previous study has found that BGN was higher expressed in endometrial cancer cells, and we also know that carcinomatous stroma and the up-regulation of BGN was significantly associated with poor tumor differentiation and advanced stage of the tumor [13]. Growing evidence has demonstrated that BGN gene is overexpressed in various carcinoma tissues such as pancreatic adenocarcinoma [8], colon tumor [9], intrahepatic cholangiocarcinoma [11], gastric cancer [12], esophageal squamous cell carcinoma [14], and melanoma [15], which have something to do with disease progression in some respects.…”
Section: Discussionmentioning
confidence: 97%
“…In our study, the circulatory levels of Biglycan in patients were significantly elevated. Liu et al 23 observed a significantly higher circulatory levels of biglycan in endometrial carcinoma which correlated with poor prognosis. Also in our study, Biglycan mRNA fold expression and tissue Biglycan protein expression by IHC and western blotting in the tumour tissue were significantly higher than those in the adjacent normal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…22 High expression of Biglycan in malignancy has been associated with poor prognosis as observed in endometrial cancer, oesophageal cancer and gastric cancer. [23][24][25] Knockdown of Biglycan using small interfering RNA (siRNA) in HCT116 colon cancer cell line inhibited cell proliferation and produced growth arrest. 26 As it also regulates the immune system, Biglycan has been found to be associated with auto-immune diseases like systemic lupus erythematosus (SLE) where it enhances the expression of CXCL13 which is a potent B cell chemo-attractant.…”
Section: Introductionmentioning
confidence: 99%
“…However, biglycan expression and serological levels of its processed byproducts correlate with the extent of liver fibrosis in murine models (108,204). Biglycan is also involved with progression and poor prognosis in a variety of malignancies such as gastrointestinal and endometrial cancers (7,122,221,377,415). In contrast, biglycan expression correlates with a favorable prognosis in bladder cancer where it seems to have an inhibitory effect on tumor cell proliferation (266).…”
Section: Proteoglycansmentioning
confidence: 99%